The Research on Cultivating Employment Ability of Chinese College Students in the New Era - Haixia, Yang (Journal of Roi Kaensarn Academi, 2024)
This study aims to explore the current status of employment ability cultivation among college students in ordinary higher education institutions in Hunan Province, China, and to investigate the relationships between students' career values, career decision-making self-efficacy, and employment ability. The research sampled 1,216 undergraduate students from five ordinary higher education institutions in Hunan Province, selected through stratified random sampling. Data was collected using the College Students' Career Values Scale, Career Decision-Making Self-Efficacy Scale, and College Students' Employment Ability Scale. Statistical analysis, including descriptive statistics, correlation analysis, and structural equation modeling, was conducted using SPSS25 and AMOS23. The study reveals that college students' career values significantly and positively influence their employment ability and career decision-making self-efficacy. Furthermore, career decision-making self-efficacy significantly affects employment ability and mediates the relationship between career values and employment ability. Based on these findings, the study suggests enhancing career education programs, fostering career decision-making skills, and developing targeted interventions to strengthen the link between career values and employment ability. These recommendations aim to provide comprehensive theoretical support and practical guidance for college students' career development and talent cultivation models in higher education, ultimately enhancing students' employment ability in the context of the new era.